Penerapan Prinsip-Prinsip Fiqh Siyasah Dalam Sistem Pendidikan Kontemporer - Marpaung, Naura Muthia Khasyi; Siti Aisyah; T. Dela Safitri; Sabila Al -Hakim; Erna Susanti (Albayan Journal of Islam and Muslim Societies, 2025)
Abtract Fiqh Siyasah is a branch of knowledge in Islam that discusses laws related to government and politics, which essentially prioritize the values of justice, deliberation, equality, accountability, and the welfare of the community. This article aims to examine the application of Fiqh Siyasah principles in the contemporary education system through a literature study approach. In the context of education, these values have an urgency to be internalized in every aspect, starting from the vision and mission of education, curriculum, institutional management, to the learning process. This study shows that the principles of siyasah such as social justice, trustworthy leadership, and active community participation are in line with the demands of the modern education system that emphasizes equal access, transparency of governance, and participation of all stakeholders. By combining the principles of Fiqh Siyasah and the needs of contemporary education, it is hoped that an education system will be formed that is not only intellectually superior but also moral, just, and oriented towards the public welfare. This article also recommends the importance of integrating Islamic political values in education policies to answer the challenges of the times in a contextual and sustainable manner.